Mergers and alliances the wider view - Woodsworth, Anne; Penniman, William David, 1937- (Emerald, 2013)
Volume 36 of Advances in Librarianship seeks to provide a comprehensive broad review of the factors that lead to mergers and other alliances, the methods used to ensure effective and successful collaborations. While corporate mergers make headlines, similar efforts in library and information science are less vociferously touted. They are occurring however amongst libraries, among LIS degree programs, and enterprises such as networks and consortia They are occurring as governments around the world mandate consolidation of operations amongst agencies under their purview in order to reduce or curtail expenditures. The chapters include original research, case studies, literature reviews and conceptual papers on the following topics: Structural and operational mergers in the US, and also in Finland where higher education has undergone significant change in the past 10 years resulting in merged and joint library operations; A review of successful and unsuccessful mergers in the corporate sector which provide lessons that benefit the nonprofit sector; Experiences in higher education in library and information science programs through analysis of collaboration both in the US and in Europe and the Middle east by multi-university effort that adhere to standards of the Bologna Process; The collapse and mergers of former OCLC regional networks in the US; ; The fiscal results and savings from network acquisition of electronic resources and databases; the impact of efforts such as the Council on Library and Information Resources to nurture collaboration amongst libraries and various types of agencies; The results of radical fiscal constraints in Greece which led to contraction and collaboration among university libraries there.
Includes index.
Keywords: Library science -- Periodicals.; Information science -- Periodicals.; elektronické knihy; electronic books